THE EFFECT OF FINANCIAL INCLUSION ON ECONOMIC GROWTH IN INDONESIA - Novia Ratna Dewi; Herman Cahyo Diartho; Zainuri Zainuri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study discusses the effect of financial inclusion, e-money infrastructure and inflation on economic growth in Indonesia, from an economics standpoint, using a quantitative approach, collecting monthly secondary data from January 2014 to December 2021, which is the starting year. The financial inclusion variable contributes up to 35% in the sixth to tenth period proving that it gives significant positive effect on the growth variable.